Spectrum of Doubly Ionized Xenon (Xe III) - Persson, W. (1988)
The spectrum of doubly ionized xenon has been investigated. The study is based on photographic recordings of xenon spectra in the 490-8900 Å range. The number of classified lines has been increased from about 300 to about 1400. The lines have been classified as transitions between 73 even levels belonging to the 5s25p4, 5s25p36p, 4ϕ, 5ϕ and 5s05p6 configurations, and 83 odd levels belonging to the 5s5p5, 5s25p36s, 7s, 5d and 6d configurations. In particular, the classifications include most of the Xe III laser lines. The experimentally observed level structures are compared with the results of Hartree-Fock calculations and least-squares fits. A comparison is also made between the results of the present analysis and the published data on the Xe N4,5OO Auger spectrum